Resection leads to less recurrence than strictureplasty in a paediatric population with obstructive crohn's. (13th March 2011) - Bamford, R; Hay, A; Kumar, D
Abstract : Introduction: Resection and Strictureplasty are used to treat patients with obstructive Crohn's disease. Strictureplasty is considered preferable in adults as it preserves bowel length. This study aims to identify differences in outcomes in children undergoing strictureplasty and resection for obstructive Crohn's disease. Methods: Patients under 20 years of age undergoing surgery between 1 st January 2000 and 1 st June 2009 were identified. Data was collected on procedures for stenotic Crohn's disease, including previous procedures outside of the original inclusion dates. Therefore operations between 12 December 1996 and 16 February 2009 are represented. Patients were divided into 2 groups; Group 1 treated with strictureplasties and group 2 resections. Postoperative complications and recurrence rates were recorded. Recurrence was defined as the need for further surgical intervention and Kaplan Meir method was used to analyse the data. Results: 26 patients and 40 operations were identified. Mean age was 15.57 years (7.2–19.4) with equal numbers of males and females. Mean follow-up was 67.44 months (10.5–156.6). 20/40 (50%) procedures involved the terminal ileum, 9/40 (22.5%) the ileo-colic junction, 8/40 (20%) the upper GI tract and 3/40 (7.5%) the colon. Mean length of stricture was 12.4 cm (5–30 cm). Group 1 consisted of 19 strictureplasties and Group 2 of 13 resections and 8 combined procedures. Significantly greater proportion of patients in group 1 required further surgery (11/19 (57.9%) versus 3/21 (14%) p=0.0086) Conclusion: Allowing for variations in disease duration, severity and previous medical management these data suggest that resection is preferable to strictureplasty in treating obstructive Crohn's disease in children and adolescents.